Application of unilateral and bilateral Plyometric exercises on the ability of planned agility and acceleration; Effectis in young soccer players - Mujezinovic, E.; Babajic, F.; Uzicanin, E.; Pavlinovic, V.; Versic, S. (SportMont, 2024)
The main aim of the study was to determine the difference in the effects between the two applied protocols (Unilateral and Bilateral), on the ability of planned agility and acceleration. For this research, the sample were active soccer players (N=30; 14 years in average). Two equal groups were formed randomly, unilateral group (EG=15) and bilateral group (CG=15). The study included an 8-week intervention of unilateral and bilateral plyometric training, applied as an integral part of soccer training, with three training sessions in one week. Both applied protocols were equalized according to the total load volume, the number of foot contacts with the ground and the character of the jump performance. Variables included tests of planned agility (side step test, and 505 test, arrowhead test), and acceleration tests (5- and 20 meters sprint). T-test for independent samples, and combined analysis of variance (2x2 / time x group) were calculated. The results showed no differences between the treatment groups, but absolute effects were achieved in both groups. The sidestep test, 505 planned agility test, arrowhead test, and 5 and 20-meter sprint test improved equally in both groups (p